2009
DOI: 10.1177/104063870902100617
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Direct and Enrichment Culture Methods for Erysipelothrix spp. from Experimentally and Naturally Infected Swine

Abstract: Abstract. The objective of the current study was to compare the diagnostic performance of a direct isolation method for Erysipelothrix spp. with a broth-based enrichment technique. Samples were obtained from three sources: 1) experimentally inoculated pigs, 2) porcine tissue samples submitted to the Iowa State University Veterinary Diagnostic Laboratory (Ames, IA), and 3) tissues from condemned carcasses at an abattoir. Culture plates from direct isolation and broth-based technique were evaluated for growth at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
2
26
0
1
Order By: Relevance
“…In addition, the sensitivity of direct culture isolation may be adversely affected by tissue conditions and antimicrobial treatment of the pig. 1 The aim of the current study was to develop and validate an immunohistochemical (IHC) assay for detection of Erysipelothrix rhusiopathiae in formalinfixed, paraffin-embedded tissue sections.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the sensitivity of direct culture isolation may be adversely affected by tissue conditions and antimicrobial treatment of the pig. 1 The aim of the current study was to develop and validate an immunohistochemical (IHC) assay for detection of Erysipelothrix rhusiopathiae in formalinfixed, paraffin-embedded tissue sections.…”
mentioning
confidence: 99%
“…?show "fnote_aff1"$^! "content-markup(./author-grp [1]/aff|./author-grp [1]/dept-list)> Erysipelothrix rhusiopathiae is a small, facultative anaerobic, Gram-positive rod that is the cause of swine erysipelas. In addition to pigs, E. rhusiopathiae has also been isolated from many species of both domestic and wild mammals, including humans, in which the disease is referred to as erysipeloid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,12,22 Standard laboratory methods (Gram staining, hydrogen sulfide production) were used to confirm Erysipelothrix spp. All isolates were serotyped by using an agar gel precipitation test as previously described.…”
mentioning
confidence: 99%
“…Immunohistochemistry techniques have been shown to be highly sensitive and specific, especially when diagnostic specimens include lesions from antimicrobial-treated pigs or chronically affected pigs (16). Our previous studies confirmed that an Erysipelothrix species-selective broth technique is more sensitive than traditional direct plating of regular and contaminated specimens (1). Although the enrichment technique has been used by other countries for a number of years, it has only recently been adopted by diagnostic laboratories within the Midwestern United States (1).…”
mentioning
confidence: 74%